What have charities ever done for us? : the stories behind the headlines - Cook, Stephen, 1949-; Mason, Tania (Policy Press, 2021)
What Have Charities Ever Done for Us? uses case studies and interviews to illustrate how charities support people and communities, foster heritage and culture and pioneer responses to crucial social, ethical and environmental questions.